Aesthetics and dementia: exploring the role of everyday aesthetics in dementia care settings. Issue 1 (2nd January 2022) - Fleetwood-Smith, Rebecka; Tischler, Victoria; Robson, Deirdre
Abstract: This paper explores how everyday aesthetics shape and are shaped within dementia care settings. The authors draw upon research that explored the significance of clothing and textiles in care home settings, to identify the varied and complex aesthetic experiences of people with dementia. The study was carried out using a series of creative, sensory and embodied research methods working with people with dementia and care home staff. Findings demonstrate that aesthetics are important in care homes at a number of levels. People with dementia discussed personal aesthetic preferences and demonstrated such preferences through embodied practices. Attending to aesthetics facilitated moments of togetherness between people with dementia and care home staff, creating person-centred encounters outside task-orientated conversations. This paper supports the importance of everyday aesthetics within dementia care settings and demonstrates that greater attention should be paid to this, to reconsider and enhance not only the look and feel of care homes and everyday items, including clothing, but also dementia care practice more broadly.